The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae) - Kompier, Tom (Zootaxa, 2018)
The occurrence in Vietnam of eight species of Asiagomphus Asahina, 1985 is discussed. Three new species are described (Asiagomphus kosterini [holotype: Da Lat, Lam Dong Prov., (appr. 11.880 N, 108.442 E), 17-IV-2016], Asiagomphus monticola [holotype: Xuan Son NP, Phu Tho Prov., (appr. 21.163 N, 104.896 E), 31-V-2014], and Asiagomphus superciliaris [holotype: Huu Lien NR, Lang Son Prov., (appr. 21.686 N, 106.376 E), 01-V-2014], and the male of Asiagomphus auricolor (Fraser, 1926) and the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 are described for the first time. The female of Asiagomphus auricolor is redescribed. Distribution and ecology of all species and a key to the males occurring in Vietnam are provided.